The Effectiveness of F-S-R (Find-Switch-Read) Technique in Improving Students’ Vocabulary Mastery at Tenth Graders of MAN 2 Wonosobo (2022) - Siti Mutoharotul Awaliyah; Arif Widyantoro (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2022)
Several obstacles that make students have difficulties in learning English, especially vocabulary mastery, encourage researcher to find appropriate and effective solutions to overcome these obstacles. The subject of this study are students of class MAN 2 Wonosobo. The main purpose of this study is to determine the effectiveness of the F-S-R (Find-Switch-Read) Technique in improving English vocabulary mastery in 10th grade students of MAN 2 Wonosobo. In addition, researcher evaluate whether the teaching methods of English in schools that have been practiced so far have been effective and efficient so that they can meet the stated teaching goals or objectives. This research is a quantitative research using experimental methods. Research data obtained from several techniques consisting of tests, experiments, and questionnaires. In this study, experiments were carried out in two classes. The two classes are divided into experimental class and control class. Researcher used pre-test as a means to test students' abilities before the experiment was conducted, and post-test to test students' abilities after the experiment was conducted. Based on the statistical calculation with the significance level 5% on Statistical Product and Service Solution (SPSS) 26, The result is indicated that the use of F-S-R (Find-Switch-Read) Teachnique is effective in improving student’ vocabulary mastery.